Pharmacotherapy of depression in palliative patients - Paulina Trawka; Aleksandra Paszkowska; Magdalena Lamch; Aleksandra Wijata; Paweł Hejnosz; Karolina Graczykowska; Magdalena Julia Jabłońska; Jakub Dorobiała; Maciej Lazarek; Michał Denkiewicz; Kornelia Kędziora-Kornatowska (Kazimierz Wielki University, 2019)
Introduction: Depression often affects people suffering from serious illnesses, including oncological and palliative patients. It reduces their quality of life and worsens their prognosis. This is why it is so important to properly treat depression in palliative patients. Material and Methods: The information provided was collected as a result of analysis of various articles and textbooks on development, diagnosis and treatment, as well as prevention of depression in terminally ill patients using Google Scholar and PubMed databases. Results: The results show that the most common drug in therapy for palliative patients with depression are the sluggish serotonin reuptake inhibitors (SSRIs). SSRIs inhibit serotonin transporter reducing serotonin reuptake. This raises the level of neurotransmitter - serotonin - in the synaptic cleft. They are well tolerated and have fewer side effects than older antidepressants (tricyclic antidepressants and monoamine oxidase inhibitors). Tricyclic antidepressants may relieve neuropathic pain and they are also beneficial for patients with insomnia. Mirtazapine in addition to antidepressant effects also causes increasing appetite, reducing nausea and sedative effect. In cancer-diagnosed patients particular attention should be paid to side effects such as nausea and vomiting that may occur in patients undergoing radiotherapy and chemotherapy using SSRIs or TCAs. SSRI therapy have a good safety profile and also interacts less frequently, while atypical antipsychotics may reduce the discomforts of taking chemotherapy. An alternative method of treating depression is the use of psychostimulants such as methylphenidate. Another way to treat depression is psychotherapy. Conclusions: There are several options for treating depression in palliative patients. It is important to pay attention to the side effects of prescribed medicines. Nevertheless, the best results are obtained by combining pharmacotherapy with psychotherapy.